Comparing rubato playing on Chopin's Nocturne, Op. 15 no. 3 in G Minor / Izzliyana Salim - Salim, Izzliyana (2022)
Rubato playing in Nocturne, Op. 15 No. 3 can be applied or interpreted differently by different performers. The dominant explanation for this is individual pianistic styles of the performer. The data of this study are obtained from journals and articles, score analysis and performance analysis. Contrary to Chopin's style of rubato playing, which is the 'melodic rubato', Sviatoslav Richter and Li Yundi used 'accelerando and rallentando' and 'tenuto and agogic accent' to perform Chopin's Nocturne, Op. 15 No. 3 in G minor. The findings of this study indicates that Chopin's rubato is no longer widely used in this century.